Social Environment and Student Satisfaction: A Study Among Religious School Students - Mohd Syafiq Zainuddin; Mazni Muhammad (International Journal of Pedagogy and Learning Community (IJPLC), 2025)
This study aims to examine the relationship between three dimensions of social environmental influence parental influence, teacher influence, and peer influence and the level of student satisfaction at a State Religious Secondary School in Malaysia. A total of 100 Form Four and Form Five students were selected using stratified random sampling to ensure balanced representation. Data were collected through a structured questionnaire and analyzed using SPSS version 27, employing descriptive statistics, Pearson correlation, and multiple linear regression analyses. The results revealed significant positive relationships between all three dimensions of social influence and student satisfaction. Among them, teacher influence showed the strongest correlation, followed by parental and peer influences. Regression analysis indicated that these dimensions collectively explained 56% of the variance in student satisfaction, with teacher influence being the most influential predictor. The findings underscore the pivotal role of teachers as facilitators who enhance students’ satisfaction and motivation. Additionally, parental support contributes significantly to students’ positive learning experiences, while peer influence mainly affects social and emotional well-being. The study recommends that school administrators and stakeholders strengthen positive social interactions and supportive environments to promote greater student satisfaction and overall well-being.